Physicochemical Attributes of Tomatoes after Different Forms of Harvesting and Transportation for Industrial Processing - Tulio de Almeida Machado; Haroldo Carlos Fernandes; Claudinei Martins Guimarães; Clarice Aparecida Megguer; Woska Pires da Costa; Fábio Lúcio Santos; Nerilson Terra Santos (PLoS ONE, 2025)
Background The mechanized harvesting and transportation of tomatoes can significantly impact their physicochemical characteristics, affecting quality and industrial processing efficiency. This study aimed to evaluate the effects of harvesting methods and transportation conditions on the firmness, titratable acidity (TA), total soluble solids (TSS – °Brix), pH, and percentage of loss of fresh mass (LFM) of tomatoes intended for industrial use. Methods The mechanized harvesting and transportation of tomatoes can significantly impact their physicochemical characteristics, affecting quality and industrial processing efficiency. This study aimed to evaluate the effects of harvesting methods and transportation conditions on the firmness, TA, TSS (°Brix), pH, and percentage of LFM in tomatoes intended for industrial use. Results Mechanized harvesting reduced tomato firmness, TA, pH, and increased mass loss. Manual harvesting resulted in 29.7% greater firmness than mechanical harvesting. The vibration effects varied depending on the floor and direction within the container, but container type did not significantly influence tomato quality. The position of the fruit in the transport medium affected firmness, with tomatoes at the rear exhibiting greater firmness and lower quality loss. Depth was negatively correlated with firmness, LFM, TA, and pH. The LFM increased with longer unloading times. Conclusion The findings highlight the need for improved handling and logistics strategies in the tomato production chain to reduce quality deterioration during harvesting and transportation. Effective interventions can minimize economic losses and increase industrial processing efficiency. Additionally, the results of this study suggest that laboratory models that use equipment such as shakers can replicate these effects for other bulk-transported crops, including fresh fruits and tubers.